2018
DOI: 10.1007/s41939-018-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

An experiment-based method for parameter identification of a reduced multiscale parametric viscoelastic model of a laminated composite beam

Abstract: Usual CAE tools simulate the behavior of composite parts from models considering the structures as being homogenized. Such approach reveals itself not to be effective when the engineer aims at determining the number of plies and the material characteristics of each ply to aim a specific dynamic behavior. To reply to this problem, we developed a multi-scale model that explicitly integrates the different design parameters of the composite structure being considered at different scales: the number of plies, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…On the other hand, the interfaces between plies are considered isotropic, so the stiffness is given by eqs. ( 9) and (10). 13…”
Section: Separated Representation Of Orthotropymentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the interfaces between plies are considered isotropic, so the stiffness is given by eqs. ( 9) and (10). 13…”
Section: Separated Representation Of Orthotropymentioning
confidence: 99%
“…We use a separated approach that leads us to consider the density ρ m only at the level of the interfaces and the density ρ f at the level of the plies; we do not use a mixture law, some experiments have demonstrated that this is sufficient to represent the dynamic behavior as shown in Fig. 7 Distribution of density [10]. Parameters holding the constitutive law of the plies p 5…”
Section: Uxmentioning
confidence: 99%
See 3 more Smart Citations